Challenges inherent to the diagnosis of antibody‐mediated rejection in lung transplantation. Issue 1 (19th February 2015) - Chin, Nicholas; Westall, Glen; Paraskeva, Miranda; Ciciulla, John; Cantwell, Linda; Snell, Greg
Abstract A bilateral sequential lung transplant was performed on a young female with cystic fibrosis‐related bronchiectasis. She had negative prospective T‐ and B‐cell crossmatch, and no known donor‐specific antibodies. Post‐transplantation, she developed bilateral pulmonary infiltrates of uncertain etiology, compounded by persistent tachycardia and questionable medication adherence. Despite aggressive intervention for suspected cellular rejection with high‐dose intravenous corticosteroid, immunoglobulin, and anti‐thymocyte globulin, her condition deteriorated to ultimately require ventilatory support. The eventual discovery of eplet donor‐recipient mismatches on related DQB1 alleles raised the diagnosis of antibody‐mediated rejection. Before plasmapheresis could be instituted, the patient rapidly succumbed to respiratory failure. Postmortem examination confirmed features of atypical allograft rejection, without evidence of classic acute cellular rejection. This is an unconventional case of antibody‐mediated lung allograft rejection – an entity that is currently a difficult diagnostic and therapeutic challenge. Prevention of donor‐specific antibodies by correct donor‐recipient matching, and optimizing adherence post‐transplantation are most important.